Interval between symptom onset and diagnosis among patients with autoimmune rheumatic diseases in a multi‐ethnic Asian population. (7th July 2021) - Xiang, Ling; Low, Andrea Hsiu Ling; Leung, Ying Ying; Fong, Warren; Gandhi, Mihir; Yoon, Sungwon; Lau, Tang Ching; Koh, Dow Rhoon; Thumboo, Julian
Abstract: Aim: The interval between symptom onset and diagnosis (pre‐diagnosis interval) can at times be longer than is ideal in patients with autoimmune rheumatic diseases (ARDs). In this study, we aimed to characterize this interval and to identify its associated factors. Method: We characterized pre‐diagnosis interval into 4 intervals: Interval #1 between symptom onset and first visit to healthcare professionals; Interval #2 between first visit to healthcare professionals and rheumatology referral; Interval #3 between rheumatology referral and first rheumatology assessment; and Interval #4 between first rheumatology assessment and diagnosis. Median regression models were used to identify factors associated with longer pre‐diagnosis interval and Interval #1. Results: Among 259 patients (median age = 52.0 [41.6‐61.9] years, 71% female, rheumatoid arthritis [n = 75], axial spondyloarthritis [axSpA] [n = 40] and psoriatic arthritis [n = 35]), median pre‐diagnosis interval was 11.5 (4.7‐36.0) months. Interval #1 (median = 4.9 months) was significantly longer than Intervals #2‐#4 (median = 0.3, 1.5, and 0.0 months, respectively). Patients with axSpA had significantly longer pre‐diagnosis interval (median = 38.7 months) and Interval #1 (median = 26.6 months) than patients with the other ARDs. Median regression suggested that patients referred from specialty care had significantly longer pre‐diagnosis interval (median difference = 7.7 months) and Interval #1 (median difference = 6.4 months) compared to those referred from primary care. Conclusion: A long pre‐diagnosis interval was observed among patients with ARDs (especially axSpA), due largely to a long interval between symptom onset and the first visit to healthcare professionals. This highlights the importance of interventions targeting patients prior to their first visit to healthcare professionals in reducing pre‐diagnosis interval.